Evaluasi Dampak Lingkungan dan Pengelolaan Limbah Pada Aktivitas Bengkel Otomotif Berbasis Prinsip Berkelanjutan - Ilmi, Nurul; Muflihat, Syakia; Baharuddin, Siti Ruqaiyah (UNM Environmental Journals, 2025)
The increasing number of motor vehicles in Indonesia has driven the growth of automotive repair shops that generate hazardous waste. This research aims to identify the types and characteristics of automotive workshop waste, evaluate waste management practices, analyze environmental impacts, and formulate a sustainability-based waste management model. The research employed a mixed-method approach on six workshops (two authorized, two medium-scale, and two small-scale) through field observations, waste volume measurements, in-depth interviews, and documentation. Results show significant variations in waste volume and types based on workshop categories, with authorized workshops having better management systems compared to medium and small-scale workshops. The main barriers to sustainable waste management implementation include cost limitations, supporting infrastructure, technical knowledge, weak regulatory supervision, and low economic incentives. The proposed management model integrates environmental, economic, and social aspects with an approach tailored to the characteristics and capacities of the workshops.